Preliminary results of new 50 MHz doppler radar experiment at Syowa Station - Ogawa, Tadahiko; Igarashi, Kiyoshi; Ose, Masami; Kuratani, Yasukazu; Fujii, Ryoichi; Hirasawa, Takeo (1983)
P(論文) A 50 MHz doppler radar newly installed at Syowa Station in 1982 is characterized by the narrow antenna beams (4°in the horizontal plane) in two different directions (approximately geomagnetic and geographic south), the three operation modes (spectrum, double-pulse and meteor mode) and the minicomputer for both real time data processing and radar control. This paper aims to check up many functions given to the radar system by presenting some preliminary results obtained at a very early stage of its operation. It is confirmed that the radar and computer systems operate as planned and are useful for continuous monitoring of the lower auroral ionosphere in the 80-120km height region. departmental bulletin paper